CRISPR/Cas9-mediated conversion of eGFP- into Gal4-transgenic lines in zebrafish - Auer, Thomas; Duroure, Karine; Concordet, Jean-Paul; Del Bene, Filippo (Nature protocols, 2014)
Here we present a protocol for the conversion of eGFP-transgenic zebrafish lines into lines expressing Gal4 from the same locus. This conversion allows the in-depth analysis of the former eGFP-expressing cell population; with the Gal4-upstream activating sequence (UAS) system, diverse UAS transgenes can be transactivated. Site-specific targeting of the gene encoding eGFP is achieved using the clustered regularly interspaced short palindromic repeats/CRISPR-associated 9 (CRISPR/Cas9) system. A single-guide RNA (sgRNA) that targets eGFP is injected into embryos together with a donor vector containing an optimized version of Gal4 (KalTA4) to trigger integration of the donor into the targeted eGFP genomic location. To enable screening for successful integration events, injection is performed in a UAS:RFP transgenic background; fish showing mosaic eGFP-to-RFP conversion are raised to adulthood. The progeny of these adult fish are then screened for stable germline transmission, and converted progeny are used to generate stable lines. We have been able to generate two stably converted transgenic lines within 4 months.
Gesehen am 14.10.2020